Kontribusi Strategi Pemasaran Instagram Ads, Celebrity Endorsement, dan Direct Marketing dalam Meningkatkan Minat Pendaftaran Siswa Baru di Al Khodijah Elementary School Kota Mojokerto - Sari, Regina Raisa; Ashriana, Ahfi Nova; Abdillah, Adil (Fakultas Ekonomi Universitas Samudra, 2025)
The purpose of this research is to find out how using a mix of direct marketing, celebrity endorsements, and Instagram ads can increase the number of new student registrations. Data from 75 respondents, gathered through both online and offline surveys, were analyzed using SPSS version 27. This study's results demonstrate that celebrity endorsement is a substantial and partially positive variable that affects interest in new student registration, although Instagram advertisements and direct marketing do not have the same effect. New student registration interest at Mojokerto City's Al Khodijah Elementary School is positively and considerably impacted by Instagram advertisements, celebrity endorsements, and direct marketing, among prospective consumers.